SETTING UP BEACH OF KOTA JOGO AS A GEMSTONE HIDDEN IN ANAKOLI VILLAGE BECOMES A LEADING DESTINATION - Bantas, Maria Goretty Diciloam; Djoa, Dominikus Djago; Bebi, Marselinus Rolando; Leli, Cristhian Roga; Titu, Archangela Giriyanti (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
The Uniflor Mengabdi Community Service Program (KKN) is a form of community engagement carried out by students at the University of Flores in collaboration with Field Supervising Lecturers (DPL). This program was designed to support the community of Anakoli Village in developing the tourism potential of Kota Jogo beach. The objective of the program is to enhance the destination's attractiveness through environmental management and the provision of simple, eco-friendly facilities grounded in local wisdom. The implementation method employed a participatory approach, actively involving the community in the stages of needs identification, program planning, activity implementation, and joint evaluation. The activities implemented included constructing waste bins, bamboo seating, photo spots in the form of swings and signage, and community service to clean the access road to Kota Jogo beach. The results of these activities demonstrated positive changes, including a cleaner coastal environment, the availability of basic tourism facilities, and increased community participation in destination management. The impact of this program is expected to increase tourist visits and create opportunities for the community to develop tourism-based businesses. Thus, the KKN program contributes to sustainable tourism development by actively involving the local community.